The Influence Of Inflation and Interest Rates and The Rupiah Exchange Rate On The Composite Stock Price Index in Indonesia - Andika Triwardana; Akbar Lufi Zulfikar; Selly Swandari (International Journal of Economics and Management Research, 2025)
This study aims to analyze the influence of macroeconomic variables, namely inflation, interest rates (BI Rate), and the Rupiah exchange rate on the Composite Stock Price Index (JCI) in Indonesia as the main indicator of the capital market. The problem in this study is to determine the extent to which the three variables affect the movement of the JCI. The data used is secondary data from 2015 to 2024 obtained from Bank Indonesia, the Central Bureau of Statistics, and the Indonesia Stock Exchange. The method used in this research is multiple linear regression analysis with the help of Eviews 12 software. The results showed that partially inflation has a positive but insignificant effect on the JCI, with a significance value of 0.9037. Interest rates have a negative and significant effect on the JCI, with a significance value of 0.0436, indicating that an increase in interest rates tends to reduce the JCI. The Rupiah exchange rate has a positive and significant effect on the JCI, indicated by a significance value of 0.0042, which means that the appreciation of the exchange rate encourages an increase in the JCI. Simultaneously, the three variables have a significant effect on the JCI, with an F-statistic probability value of 0.020178. This finding confirms that fluctuations in interest rates and exchange rates play an important role in influencing the Indonesian stock market, while the influence of inflation tends to be weak. The conclusion of this study is that interest rates and exchange rates are significant macroeconomic indicators that need to be considered in investment strategies and economic policies. The R-squared value of 0.783985 indicates that the three variables of inflation, interest rates and rupiah exchange rate contribute 78.39% to the IHSG, while the remaining 21.61% is influenced by other factors.